Электронный информационно-поисковый тезаурус предметной области «сверхтвердые материалы» как формальная система знаний - Колодницкий, В.Н.; Кулаковский, В.Н.; Лебедева, А.А.; Чистяков, Е.М.; Гордашник, К.З.; Скворцов, И.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
An electronic multilingual information retrieval thesaurus for the system of materials science of the Superhard Materials ontology that includes the concepts of the problem-oriented knowledge, which correspond to the scientific directions, developed at the Bakul Institute for Superhard Materials, National Academy of Sciences of Ukraine has been created.